1995
DOI: 10.1113/jphysiol.1995.sp020986
|View full text |Cite
|
Sign up to set email alerts
|

The effects of anaemia on heart, placenta and body weight, and blood pressure in fetal and neonatal rats.

Abstract: 1. Reports that maternal anaemia in pregnancy is associated with a greater placental: birth weight ratio, which predisposes towards high postnatal blood pressure in the human, led us to examine the effects of maternal anaemia during pregnancy on placental size, fetal and neonatal growth, and blood pressure development in the rat. 2. Nutritional anaemia was induced in female rats prior to mating and maintained throughout pregnancy and up until weaning of the pups. Fetuses were studied at 20 days of gestation (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 14 publications
9
78
5
Order By: Relevance
“…The enlarged hearts in the PID animals during the neonatal period are consistent with reports by others 5,7,9,22 and may be an adaptive response to anemia during gestation and the neonatal periods. Indeed, fetal anemia has been shown to increase heart weight and cardiac output in sheep.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The enlarged hearts in the PID animals during the neonatal period are consistent with reports by others 5,7,9,22 and may be an adaptive response to anemia during gestation and the neonatal periods. Indeed, fetal anemia has been shown to increase heart weight and cardiac output in sheep.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, studies in rats have shown that inadequate iron supply during early development can produce hypertension, even when iron levels are subsequently normalized. [5][6][7][8][9][10] In fact, Lisle et al 8 demonstrated that PID produced both a nephron deficit and elevated blood pressure in adult offspring. Although the effects of PID on renal function were not investigated, the study by Lisle et al 8 implicates the developing kidney as a potential target for perinatal insult.…”
mentioning
confidence: 99%
“…Surprisingly, Pcm mutant animals exhibited a severe iron deficiency at birth, more severe in homozygotes (Mok et al, 2004). Because fetal iron and other nutrient requirements are met by placental transport from the maternal to fetal blood circulation, maternal Development 131 (19) Research article iron deficiency exerts profound effects on fetal as well as postnatal development (Crowe et al, 1995) (for a review, see McArdle et al, 2003). Interestingly, fetuses exhibit decreased severity of iron deficiency in comparison to the mother, indicating the presence of regulatory mechanisms to sustain an adequate supply of iron to the fetus (Gambling et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Undernutrition in pregnancy results in IUGR and high BP in adult life in sheep (65), rats (86), and guinea pigs (40) and a reduced life span in rats (4,149). Fetal hypoxia, induced by unilateral uterine artery ligation in guinea pigs (115), aortic ligation in rats (5), uterine artery ligation in rats (70), removal of endometrial caruncles in sheep (125), maternal hypobaric hypoxia in rats (151), and iron deficiency anemia in rats (32,95) are also associated with IUGR and hypertension later in life. Together, these observations point at metabolism and oxygen supply as central factors.…”
Section: Experimental Evidence Of Programmingmentioning
confidence: 99%